Molybdenum-doped nano zinc oxide with high visible light photocatalytic performance as well as preparation method and application of molybdenum-doped nano zinc oxide

By doping molybdenum-doped nano zinc oxide and synthesizing molybdenum-doped nano zinc oxide by one-pot method, the problem of low photocatalytic activity of zinc oxide in the visible light region is solved, and efficient visible light photocatalytic effect and a simple preparation process are achieved.

CN119793438AActive Publication Date: 2025-04-11SOUTH CHINA UNIV OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411807318.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Zinc oxide has low photocatalytic activity in the visible light region, limiting its application potential.

Method used

By doping molybdenum elements, local surface plasmon resonance peaks are generated to improve the absorption capacity of zinc oxide to visible light, and a one-pot method is used to synthesize molybdenum-doped nano zinc oxide.

Benefits of technology

The visible light utilization rate and photocatalytic efficiency of zinc oxide are significantly improved, and the rhodamine B can be effectively degraded, and the preparation method is simple and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793438A_ABST
    Figure CN119793438A_ABST
Patent Text Reader

Abstract

The invention discloses molybdenum-doped nano-zinc oxide with high visible light photocatalytic performance as well as a preparation method and application of the molybdenum-doped nano-zinc oxide. The molybdenum-doped nano zinc oxide is prepared by the following steps: carrying out vacuum degassing treatment on 1-octadecene, 1-dodecanol, oleic acid, a zinc source and a molybdenum source, uniformly stirring in a nitrogen atmosphere, heating to 100-140 DEG C, carrying out heat preservation until solid particles are dissolved, heating to 220-250 DEG C, carrying out heat preservation reaction for 0.5-1 hour, cooling, washing and drying. According to the molybdenum-doped nano zinc oxide, zinc oxide generates a local surface plasmon resonance absorption peak within the range of 600-700 nm through molybdenum ion doping, and the diameter of nano powder is 5-20 nm; the visible light photocatalytic performance of the zinc oxide material is greatly improved under the condition of visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis, and in particular to a molybdenum-doped nano zinc oxide with high visible light photocatalytic performance, and a preparation method and application thereof. Background Art

[0002] Photocatalysis is a technology that uses light energy to drive chemical reactions. It is widely used in environmental governance, energy conversion, chemical synthesis and other fields. Zinc oxide (ZnO) has become a potential photocatalytic material due to its good optical properties, wide band gap (about 3.37 eV), high chemical stability and environmental friendliness. The photocatalytic mechanism of ZnO is mainly based on its ability to absorb ultraviolet light to excite electrons to the conduction band and generate electron-hole pairs on the surface. These carriers can participate in the degradation of organic pollutants or water decomposition reactions. However, the wide band gap of ZnO means that it can only effectively absorb ultraviolet light, which limits its photocatalytic activity in the visible light region.

[0003] In order to solve the limitations of ZnO in photocatalytic applications, the prior art attempts to dope or modify ZnO by various means to broaden its light absorption range and improve the photocatalytic efficiency. Chinese invention patent application 202411178170.9 discloses a cobalt-doped nano zinc oxide and its green synthesis method and application. Chinese invention patent CN112499664B discloses a cuprous oxide-doped nano zinc oxide composite material and its preparation method. Chinese invention patent application CN201410431213.X discloses a method for preparing molybdenum-doped zinc oxide film by magnetron sputtering, but its high transmittance in the visible light region makes it difficult to achieve visible light photocatalysis. The present invention synthesizes molybdenum-doped nano zinc oxide with oxygen vacancies through a one-pot method, produces a localized surface plasmon resonance absorption peak in the visible light region, and achieves its photocatalytic effect in the visible light.

[0004] Chinese invention patent CN113559913B discloses a sandwich structure of nitrogen-doped zinc oxide coated nitrogen-doped graphene composite material and its preparation method and application, which composites zinc oxide with graphene, broadens the light response range of zinc oxide to visible light through nitrogen doping, and uses nitrogen-doped graphene to load zinc oxide to promote its photogenerated electron transmission, thereby improving the visible light photocatalytic efficiency of zinc oxide. However, the preparation steps of the graphene composite material of this technology are cumbersome and costly, and the preparation time is as long as 15 hours and requires a high temperature of 600°C. Summary of the invention

[0005] The purpose of the present invention is to provide a simple and easy-to-implement molybdenum-doped nano zinc oxide with high visible light photocatalytic performance and a preparation method thereof, which significantly improves the visible light utilization rate of the zinc oxide material.

[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0007] The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance is prepared by vacuum degassing 1-octadecene, 1-dodecanol, oleic acid, a zinc source and a molybdenum source, uniformly stirring under a nitrogen atmosphere, heating to 100-140° C., keeping the temperature until the solid particles are dissolved, heating to 220-250° C. and keeping the temperature for 0.5-1 h, and cooling, washing and drying.

[0008] To further achieve the purpose of the present invention, preferably, the molar ratio of 1-octadecene, zinc source, 1-dodecanol, oleic acid and molybdenum source is (6.6-44):1:(7.2-11.2):(3-4):(0.05-0.35).

[0009] Preferably, the zinc source is one or more of zinc stearate and zinc acetylacetonate.

[0010] Preferably, the molybdenum source is one or more of molybdenum acetylacetonate, ammonium molybdate and sodium molybdate.

[0011] Preferably, the vacuum degassing treatment time is 1-3 minutes.

[0012] Preferably, the time for maintaining the temperature at 100-140° C. until the solid particles are dissolved is 20-30 minutes.

[0013] Preferably, the cooling method is to cool to 30-70°C at room temperature while keeping nitrogen flowing; the drying is to dry naturally at room temperature for more than 20 minutes or to dry in vacuum at 60-80°C for 15-60 minutes.

[0014] Preferably, the washing is to cool the reactants and fully mix them with a mixed solution of n-hexane and ethanol in a volume ratio of 1:1.5-5, centrifuge at a speed of 5000-10000 r / mins for 5-10 mins; repeatedly mix the centrifuged product with the mixed solution of n-hexane and ethanol and then centrifuge for 2-4 times.

[0015] The method for preparing the molybdenum-doped nano zinc oxide with high visible light photocatalytic performance comprises the following steps:

[0016] 1) using 1-octadecene as solvent, 1-dodecanol as activator, oleic acid as ligand, mixing with zinc source and molybdenum source, and performing vacuum degassing treatment;

[0017] 2) stirring the product obtained in step 1) evenly under a nitrogen atmosphere, heating to 100-140° C., and keeping the temperature until the solid particles in the raw material are dissolved, and then raising the temperature to 220-250° C. and keeping the temperature for 0.5-1 h;

[0018] 3) Cooling, washing and drying the product obtained in step 2) to obtain molybdenum-doped nano zinc oxide with high visible light photocatalytic performance.

[0019] The application of the molybdenum-doped nano zinc oxide with high visible light photocatalytic performance in the degradation of rhodamine B.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The present invention generates a localized surface plasmon resonance peak with a peak value at 600-700nm by doping with molybdenum element, thereby generating a strong absorption effect on visible light, thereby achieving the purpose of photocatalytic degradation of rhodamine B.

[0022] 2) The molybdenum-doped nano zinc oxide powder of the present invention is prepared by introducing metal ions Mo 6+ / 5+ / 4+ Doping replaces Zn in the original lattice 2+ , which greatly increases the free carrier concentration in the zinc oxide semiconductor, causing it to produce strong localized plasma resonance absorption in the visible light region. The absorbance in the visible light region is affected by the amount of molybdenum source used. The absorption of visible light by the product can be changed by adjusting the molybdenum doping amount, thereby adjusting the photocatalytic degradation performance of the molybdenum-doped nano-zinc oxide photocatalyst for rhodamine B.

[0023] 3) The present invention adopts a one-pot method to successfully incorporate molybdenum ions into zinc oxide through a ligand and an activator, and improves the crystallinity of ZnO by using an organic solvent to achieve the transformation of the zinc precursor to ZnO.

[0024] 4) The molybdenum-doped nano zinc oxide photocatalyst sample synthesized by the present invention is very stable and can be placed for a long time. The preparation method is simple, the equipment requirements are low, and the synthesis cycle is short.

[0025] However, the preparation steps of the graphene composite material of this technology are complicated and costly, the preparation time is as long as 15 hours and a high temperature of 600°C is required. The present invention can directly prepare a doped zinc oxide material with high visible light photocatalytic effect within 2 hours at 220-250°C through a one-step synthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray diffraction patterns of the nano zinc oxide samples obtained in the comparative example, example 1, example 2, example 3, and example 4 are shown.

[0027] Figure 2a This is a transmission electron microscope image of the product sample obtained in Example 2.

[0028] Figure 2b This is the interplanar spacing diagram of the product sample obtained in Example 2.

[0029] Figure 3The absorbance spectra of the nano zinc oxide powders obtained in Comparative Example 1, Example 1 and Example 2 after being prepared into dispersion liquids are shown.

[0030] Figure 4 The degradation curves of 20 mg / L Rhodamine B solution itself under a xenon lamp and the degradation of Rhodamine B in the comparative example, Example 1 and Example 2 under a xenon lamp are shown.

[0031] Figure 5 It is a first-order kinetic curve diagram of the degradation of Rhodamine B in the comparative example, example 1 and example 2 under a xenon lamp. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with embodiments and drawings to illustrate and explain the present invention, but the embodiments of the present invention are not limited thereto.

[0033] The present invention adopts the method of thermal decomposition of organic metal precursor in non-polar solvent 1-octadecene to dope molybdenum ions into zinc oxide, and centrifugal washing and drying can obtain molybdenum-doped nano zinc oxide material. The utilization efficiency of visible light and visible light photocatalytic performance of the modified zinc oxide are greatly improved. Under high temperature conditions, due to the Mo 6+ Mo 5+ Mo 4+ With Zn 2+ The ionic radius of Mo is close to 6+ It will enter the ZnO network during the process of raw material hydrolysis and replace the Zn 2+ ions, introduce defects, due to Mo 6+ / 5+ / 4+ Zn in the original ZnO lattice 2+ The unequal substitution will introduce a large number of free electrons. The specific defect equation is shown below:

[0034]

[0035] Mo 6+ +e'→Mo 5+

[0036]

[0037] Mo 5+ +e'→Mo 4+

[0038]

[0039] The present invention uses metal cation doping to make the pure zinc oxide material, which has no absorption in the visible light range, produce a surface localized plasma resonance absorption peak in the range of 600-700nm, and the diameter of the nano powder is 5-20nm. The photocatalytic performance of the zinc oxide material in the visible light range is greatly improved. According to the Drude-Lorentz theory, the localized surface plasma resonance peak will redshift with the increase of the dielectric constant of the surrounding environment.

[0040] The method of the invention has simple process, is easy to implement and has high practical application value.

[0041] The examples and comparative examples of the present invention were prepared and tested in the same manner, and the test methods for the absorbance and photocatalytic performance of the samples were as follows:

[0042] The absorbance of the dispersion prepared from the sample was tested using an ultraviolet-visible-near-infrared spectrophotometer. 0.02 g of nano zinc oxide powder was dispersed in 10 ml of tetrachloroethylene solution in the presence of 0.1 ml of oleic acid and oleylamine, and the mixture was shaken well. After completion, the absorbance of the dispersion was tested using an ultraviolet-visible-near-infrared spectrophotometer.

[0043] 0.05 g of the material prepared in each embodiment was weighed and placed in a beaker, and then a rhodamine solution with a concentration of 20 mg / L was added, and magnetic stirring was performed for 1 h in the dark to reach adsorption equilibrium. Subsequently, a 300 W fluorene lamp was used as a visible light source, the lamp was 15 cm away, the rhodamine solution was irradiated with the light, the solution was taken out from the beaker every 15 minutes, the irradiation was continued, and the concentration of the rhodamine solution at different illumination times was measured using a Cary 60 UV-visible spectrophotometer produced by Agilent, and the visible light photocatalytic performance of the prepared material was evaluated based on the measured rhodamine concentration.

[0044] In order to better compare the photocatalytic efficiency of different catalysts, the degradation of Rhodamine B solution in water was kinetically analyzed. A scatter plot was drawn with ln(C0 / C) as the ordinate and time t(mins) as the abscissa, and fitting was performed. The kinetic linear simulation curves of the photocatalytic degradation of Rhodamine B by different catalysts showed that ln(C0 / C) was linearly related to the catalytic time t. Due to the low initial concentration of the reactants, the above degradation reaction conformed to the Langmuir-HinShelwood apparent first-order kinetic model. The simplified apparent first-order kinetic model is:

[0045] ln(C0 / C)=k app t

[0046] C0 is the initial concentration of the reactant (mg / L), C is the concentration of the reactant at time t (mg / L), k app is the apparent first-order rate constant, and t is the reaction time (illumination time).

[0047] Comparative Example

[0048] Zinc oxide from Fuchen Chemical Reagent Factory was used. This comparative example had no absorption peak in the visible light and the apparent rate constant was 0.0004mins -1 .

[0049] Example 1

[0050] A method for preparing molybdenum-doped nano zinc oxide with high visible light photocatalytic performance, the steps are as follows:

[0051] 1) Weigh 4.8 g 1-dodecanol, 21 ml 1-octadecene, and 2.65 g oleic acid into a 250 ml three-necked flask, and then add 3 mmol zinc stearate and 0.15 mmol molybdenum acetylacetonate into the three-necked flask, with a molar ratio of molybdenum to zinc of 0.05.

[0052] 2) Place the three-necked flask in a heat-collecting constant temperature heating magnetic stirrer, vacuum degas for 1 minute, introduce nitrogen, heat in an oil bath and stir, heat to 100°C and keep warm for 20 minutes until all the solid particles are dissolved;

[0053] 3) After the previous step is completed, continue to introduce nitrogen for heating, and keep the temperature for 0.5h after the temperature rises to 220°C. After the reaction is completed, the product is naturally cooled to 26°C, and the reactant is fully mixed with a mixed solution of n-hexane and ethanol in a volume ratio of 1:1.5, and then centrifuged at a speed of 5000r / mins for 5mins. Repeat the mixing of the centrifuged product with the mixed solution of n-hexane and ethanol in the above ratio and centrifuge it twice. Finally, the centrifuged sample is naturally dried for 20mins to obtain a product, which is a molybdenum-doped nano-zinc oxide photocatalyst.

[0054] Example 2

[0055] A method for preparing molybdenum-doped nano zinc oxide with high visible light photocatalytic performance, the steps are as follows:

[0056] 1) Weigh 4.8 g 1-dodecanol, 21 ml 1-octadecene, and 2.65 g oleic acid into a 250 ml three-necked flask, and then add 3 mmol zinc stearate and 1.05 mmol molybdenum acetylacetonate into the three-necked flask, with a molar ratio of molybdenum to zinc of 0.35.

[0057] 2) Place the three-necked flask in a heat-collecting constant temperature heating magnetic stirrer, vacuum degas for 3 minutes, introduce nitrogen, heat in an oil bath and stir, heat to 140°C and keep warm for 30 minutes until all the solid particles are dissolved;

[0058] 3) After the previous step is completed, continue to introduce nitrogen for heating, and keep the temperature for 0.5h after the temperature rises to 250°C. After the reaction is completed, the product is naturally cooled to 26°C, and the reactant is fully mixed with a mixed solution of n-hexane and ethanol in a volume ratio of 1:1.5, and then centrifuged at a speed of 10000r / mins for 10mins. Repeat the mixing of the centrifuged product with the mixed solution of n-hexane and ethanol in the above ratio and centrifuge it again for 4 times. Finally, the centrifuged sample is naturally dried for 60mins to obtain a product, which is a molybdenum-doped nano zinc oxide photocatalyst.

[0059] Example 3

[0060] A method for preparing molybdenum-doped nano zinc oxide with high visible light photocatalytic performance, the steps are as follows:

[0061] 1) Weigh 4.8 g 1-dodecanol, 21 ml 1-octadecene, and 2.65 g oleic acid into a 250 ml three-necked flask, and then add 3 mmol zinc stearate and 0.15 mmol molybdenum acetylacetonate into the three-necked flask, with a molar ratio of molybdenum to zinc of 0.05.

[0062] 2) Place the three-necked flask in a heat-collecting constant temperature heating magnetic stirrer, vacuum degas for 3 minutes, introduce nitrogen, heat in an oil bath and stir, heat to 140°C and keep warm for 30 minutes until all the solid particles are dissolved;

[0063] 3) After the previous step is completed, continue to introduce nitrogen for heating, and keep the temperature for 1 hour after the temperature rises to 250°C. After the reaction is completed, the product is naturally cooled to 26°C, and the reactant is fully mixed with a mixed solution of n-hexane and ethanol in a volume ratio of 1:5, and then centrifuged at a speed of 5000r / mins for 5mins. Repeat the mixing of the centrifuged product with the mixed solution of n-hexane and ethanol in the above ratio and centrifuge it twice. Finally, the centrifuged sample is vacuum dried at 60°C for 15mins, and the resulting product is a molybdenum-doped nano-zinc oxide photocatalyst.

[0064] Example 4

[0065] A method for preparing molybdenum-doped nano zinc oxide with high visible light photocatalytic performance, the steps are as follows:

[0066] 1) Weigh 4.8 g of 1-dodecanol, 21 ml of 1-octadecene, and 2.65 g of oleic acid into a 250 ml three-necked flask, and then add 3 mmol of zinc acetylacetonate and 0.15 mmol of molybdenum acetylacetonate into the three-necked flask, with a molar ratio of molybdenum to zinc being 0.05.

[0067] 2) Place the three-necked flask in a heat-collecting constant temperature heating magnetic stirrer, vacuum degas for 3 minutes, introduce nitrogen, heat in an oil bath and stir, heat to 140°C and keep warm for 30 minutes until all the solid particles are dissolved;

[0068] 3) After the previous step is completed, continue to introduce nitrogen for heating, and keep the temperature for 0.5h after the temperature rises to 220°C. After the reaction is completed, the product is naturally cooled to 26°C, and the reactant is fully mixed with a mixed solution of n-hexane and ethanol in a volume ratio of 1:5, and then centrifuged at a speed of 10000r / mins for 10mins. Repeat the mixing of the centrifuged product with the mixed solution of n-hexane and ethanol in the above ratio and centrifuge it again for 4 times. Finally, the centrifuged sample is vacuum dried at 80°C for 60mins to obtain a product, which is a molybdenum-doped nano-zinc oxide photocatalyst.

[0069] Example 5

[0070] A method for preparing molybdenum-doped nano zinc oxide with high visible light photocatalytic performance, the steps are as follows:

[0071] 1) Weigh 4.8 g 1-dodecanol, 21 ml 1-octadecene, and 2.65 g oleic acid into a 250 ml three-necked flask, and then add 3 mmol zinc acetylacetonate and 1.05 mmol molybdenum acetylacetonate into the three-necked flask, with a molar ratio of molybdenum to zinc being 0.35.

[0072] 2) Place the three-necked flask in a heat-collecting constant temperature heating magnetic stirrer, vacuum degas for 3 minutes, introduce nitrogen, heat in an oil bath and stir, heat to 140°C and keep warm for 30 minutes until all the solid particles are dissolved;

[0073] 3) After the previous step is completed, continue to introduce nitrogen for heating, and keep the temperature for 0.5 hours after the temperature rises to 250°C. After the reaction is completed, the product is naturally cooled to 26°C, and the reactant is fully mixed with a mixed solution of n-hexane and ethanol in a volume ratio of 1:3, and then centrifuged at a speed of 10000r / mins for 5 minutes. Repeat the mixing of the centrifuged product with the mixed solution of n-hexane and ethanol in the above ratio and centrifugation for 2 times. Finally, the centrifuged sample is naturally dried for 20 minutes to obtain a product, which is a molybdenum-doped nano-zinc oxide photocatalyst.

[0074] Figure 1 The X-ray diffraction patterns of the comparative examples 1, 2, 3 and 4 are all corresponding to the diffraction peaks of wurtzite-type zinc oxide (JCPDS: 36-1451), belonging to the hexagonal system. The doping of molybdenum ions will not change the crystal form of zinc oxide. On the other hand, the diffraction angle of the (101) crystal plane of the sample doped with molybdenum (Example 1) has begun to shift toward a small angle compared to the pure zinc oxide sample (Comparative Example 1). With the further introduction of molybdenum ions (Example 2), the peak position of the diffraction peak shifts more. It can be seen from the Bragg equation 2dsinθ=nλ that θ decreases and the interplanar spacing d increases. This is because after doping with Mo 6+ / 5+ / 4+ Replaces Zn in the zinc oxide lattice2+ , causing the lattice to expand and thus increase the interplanar spacing. Figure 3 From the absorbance spectra of each sample, it can be seen that compared with the pure zinc oxide sample of the comparative example, the absorbance curve of the doped sample has undergone a significant change in the visible light region, which is due to the local plasma resonance phenomenon, which proves that the synthesized Examples 1, 2, 3, and 4 are the corresponding molybdenum-doped wurtzite zinc oxide.

[0075] Figure 2a and Figure 2b They are the morphology and size diagram and the inter-crystalline spacing diagram of the sample obtained in Example 2, respectively. It can be seen that the particle shape of the molybdenum-doped nano-zinc oxide powder synthesized at 250° C. is soybean-shaped with a diameter of 5-20 nm.

[0076] Figure 3 The absorbance spectra of the solutions prepared from the samples obtained in the comparative example, example 1 and example 2 are shown. The pure zinc oxide sample (comparative example 1) has no absorption peak in the visible light, while the molybdenum-doped zinc oxide has an absorption peak near 650nm.

[0077] Figure 4 The following is a degradation curve of Rhodamine B degradation under xenon lamp visible light irradiation in Comparative Example, Example 1, Example 2, Example 3, Example 4, and Example 5. Figure 5 for Figure 4 Corresponding first-order kinetic curve. Under the irradiation of xenon lamp, pure zinc oxide (comparative example) was almost not degraded in 90 minutes; molybdenum-doped nano zinc oxide improved the photocatalytic performance of pure zinc oxide to varying degrees, Example 1 degraded 59.65% in 90 minutes, Example 2 degraded 75.31% in 90 minutes, Example 3 degraded 56.33% in 90 minutes, Example 4 degraded 60.51% in 90 minutes, and Example 5 degraded 75.39% in 90 minutes. The apparent rate constants of Example 1, Example 2, Example 3, Example 4, and Example 5 were 0.01006 min, respectively. -1 , 0.01665min -1 , 0.00906min -1 , 0.01086min -1 , 0.01551min -1 They are pure zinc oxide catalyst (0.00044min -1 ) by 23, 38, 21, 25, and 36 times, indicating that the photocatalytic rate of molybdenum-doped nano-zinc oxide is significantly improved, proving that the photocatalytic degradation performance of zinc oxide nanopowders can be improved by doping with molybdenum ions.

[0078] The test results of the embodiments of the present invention and the accompanying drawings show that the present invention prepares molybdenum-doped nano zinc oxide materials through a simple one-step synthesis, and the synthesis process is simple and easy to implement. At the same time, the present invention improves the utilization efficiency of zinc oxide for visible light, and obtains a material with high visible light photocatalytic effect, which has good application prospects.

[0079] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. Molybdenum-doped nano zinc oxide with high visible light photocatalytic performance, characterized in that: The method comprises vacuum degassing of 1-octadecene, 1-dodecanol, oleic acid, a zinc source and a molybdenum source, uniformly stirring under a nitrogen atmosphere, heating to 100-140° C., keeping the temperature until solid particles are dissolved, heating to 220-250° C., keeping the temperature for reaction for 0.5-1h, cooling, washing and drying to obtain the product.

2. The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to claim 1, characterized in that: The molar ratio of 1-octadecene, zinc source, 1-dodecanol, oleic acid and molybdenum source is (6.6-44):1:(7.2-11.2):(3-4):(0.05-0.35).

3. The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to claim 1, characterized in that: The zinc source is one or more of zinc stearate and zinc acetylacetonate.

4. The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to claim 1, characterized in that: The molybdenum source is one or more of molybdenum acetylacetonate, ammonium molybdate and sodium molybdate.

5. The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to claim 1, characterized in that: The vacuum degassing treatment time is 1-3 minutes.

6. The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to claim 1, characterized in that: The time for maintaining the temperature at 100-140° C. until the solid particles are dissolved is 20-30 minutes.

7. The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to claim 1, characterized in that: The cooling method is to keep nitrogen flowing and cool to 30-70°C at room temperature; the drying is to dry naturally at room temperature for more than 20 minutes or to dry in vacuum at 60-80°C for 15-60 minutes.

8. The molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to claim 1, characterized in that: The washing process comprises the following steps: the reaction product is cooled, fully mixed with a mixed solution of n-hexane and ethanol in a volume ratio of 1:1.5-5, and centrifuged at a speed of 5000-10000 r / mins for 5-10 minutes; the mixed solution of n-hexane and ethanol is repeatedly mixed with the centrifuged product and then centrifuged 2-4 times.

9. The method for preparing the molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to any one of claims 1 to 8, characterized in that The steps include: 1) 1-octadecene is used as a solvent, 1-dodecanol is used as an activator, oleic acid is used as a ligand, mixed with a zinc source and a molybdenum source, and subjected to vacuum degassing treatment; 2) stirring the product obtained in step 1) evenly under a nitrogen atmosphere, heating to 100-140° C., and keeping the temperature until the solid particles in the raw material are dissolved, and then raising the temperature to 220-250° C. and keeping the temperature for 0.5-1 h; 3) Cooling, washing and drying the product obtained in step 2) to obtain molybdenum-doped nano zinc oxide with high visible light photocatalytic performance.

10. Use of the molybdenum-doped nano zinc oxide with high visible light photocatalytic performance according to any one of claims 1 to 9 in the degradation of rhodamine B.

Citation Information

Patent Citations

  • Method for preparing molybdenum-doped zinc oxide film by magnetron sputtering method

    CN104213090A

  • A cuprous oxide-doped zinc oxide nanocomposite material and its preparation method

    CN112499664B

  • A sandwich-structured nitrogen-doped graphene composite material, its preparation method and application

    CN113559913B

  • Cobalt-doped nano zinc oxide as well as green synthesis method and application thereof

    CN118719073A

  • Nickel-doped zinc oxide hierarchical structure photocatalytic nano-material and preparation method thereof

    CN103657662A